Peningkatan Teknologi Pendidik Pesantren Anak Sholeh melalui MEMRiSE: Coaching & Training - Hesty Puspita Sari; Wawan Herry Setiawan (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
Mastering technology improvement is something that educators have to continue to strive for on an ongoing basis. A teacher is required to master the use and applicate the science and technology development along the revolution industrial era 4.0. To continue improving the quality of self, a teacher needs to be given coaching and training. The training activity with the theme "Introduction to English Language Learning Technology at the Pesantren Anak Sholeh, a kindergarden and primary school in Ponorogo" was attended by Ustadz and Ustadzah of the Pesantren Anak Sholeh for PAUD and Elementary School levels with a total of 12 participants. The coaching and training was carried out on Saturday, August 7, 2021 by introducing MEMRiSE as a very easy learning application that children can do to improve their English and Arabic vocabulary. Participants were given the opportunity directly to practice downloading and trying the MEMRiSE application and practice it. Based on the results of the activities, participants showed high enthusiasm in practicing the use of MEMRiSE and stated the ease of learning to increase children's vocabulary. In general, educators at the Sholeh Children's Islamic Boarding School have carried out creativity and learning innovation using MEMRiSE. The results of the responses from the coaching and training participants also showed 100% that MEMRiSE was motivating, fun for learning and very effective in learning trough online in the covid-19 pandemic situation.